High-speed rail and high-tech industry evolution: Empirical evidence from China. (June 2021) - Xiao, Fan; Lin, Jen-Jia
Highlights: The development of regional high-tech industries in China was a path-breaking process. High-speed rail changed the high-tech industry evolution from path-breaking to path-dependence. The impact of HSR on the high-tech industry evolution was more significant at the city scale than the province scale. Abstract: Launching high-speed rail (HSR) services leads to time–space compression and contributes in the reconstruction of economic activities. This research explored the relationship between HSR and high-tech industry evolution. By using relatedness and HSR accessibility indicators, this study collected a panel data set of 286 cities and 31 provinces in China and covered the period 2008–2016, estimated two-way fixed effect models at the city and province scales, and clarified the role of HSR in the high-tech industry evolution. Empirical results were as follows. (1) The development of high-tech industries in China was a path-breaking process. (2) HSR changed the high-tech industry evolution from path-breaking to path-dependence. (3) The impact of HSR on the high-tech industry evolution was more significant at the city scale than the province scale. Current findings broaden our understanding of the associations of transport infrastructures with high-tech industry evolution in an emerging large-scale economy.